Executividade da sentença de "improcedência" proferida no processo civil - Silva, Rinaldo Mouzalas de Souza e (2013)
The present work aims to demonstrate, through indirect research (literature and documents), that is possible to execute the judgment of dismissal rendered in civil proceedings when recognized benefit entitlement in favor of the defendant. Therefore, it shows that the defendant may be contemplated by the offer of jurisdiction, even when it has not made a request, and that the negative statement of subjective rights claimed by the author may mean recognition of law in favor of the defendant, enforceable.